Варлам Шаламов - Шкловский Евгений Александрович (Новое в жизни, науке, технике, 1991)
Экземпляры: ФИЛ (20110802) / Инвентарный номер: 987462 / Цена: 0.30 / Сис.шифр: 83.3(2=Рус)7-8 / Авт.знак: Ш 66 / ГРНТИ: 17 / ББК: 83.3(2=Рус)6-8